HEADPLAY Personal Cinema System Facilitates Intravenous Cannulation in Children: A Randomized Controlled Trial - Evangeline Lim; Teddy Fabila; Thong Sze Ying; Josephine Tan (Hindawi Limited, 2013)
HEADPLAY personal cinema system (PCS) is a portable visual headset/visor through which movie clips may be viewed. We studied the use of HEADPLAY PCS as a distraction tool in facilitating intravenous cannulation in children undergoing anaesthesia. 60 children were enrolled into the study and randomized into 2 groups. EMLA local anaesthetic cream was used to reduce the pain associated with intravenous cannulation. Children in group 1 wore the HEADPLAY visor whereas children in group 2 were subject to conventional distraction therapy. Children were asked to rate their anxiety, pain, and satisfaction scores after intravenous cannulation. Periprocedural anxiety was also determined using the modified Yale Preoperative Anxiety Scale (mYPAS). There were no statistically significant differences in terms of pain and anxiety scores between the 2 groups. Although the satisfaction score of the children in the HEADPLAY PCS group was marginally higher compared to the conventional group, this did not hit statistical significance. 86.6% of children in group 1 reported that they would want to use the visor again for their next intravenous cannulation. We conclude that HEADPLAY PCS is a distraction tool that is acceptable to most children and can contribute towards satisfaction of the intravenous cannulation process in children.